KONTRIBUSI PEMUNGUTAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH DI KOTA PAREPARE - Wijaya, Ilham (Universitas Muhammadiyah Parepare, 2019)
Regional Retribution on Regional Original Income of Parepare City in the period 2010-2017. Receipt of fees in research are business services, general services and licensing. The assessment method is quantitative research, where data are analyzed by calculating the amount of service fees, general services and licensing. Data collection technique. A (direct) review of the object of research, namely the Regional Financial Board of the Municipality of Parepare. The results of the study show that business service fees, general services and other licensing fees for the period 2011-2017 contributed less to the original income of the City of Parepare. The contribution rate of 53% in the criteria was very good only in 2011, whereas in 2012-2017 it contributed less.